Challenges of ICT & Teacher Education Curriculum: The Impact of Globalization and Technological Change on Teacher Education Curriculum (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Globalization and technological change-processes that have accelerated in tandem over the past fifteen years-have created a new global economy powered by technology, fuelled by information and driven by knowledge. The emergence of this new global economy has serious implications for the nature and purpose of teacher educational institutions. As the half-life of information continues to shrink and access to information continues to grow exponentially, these institutions cannot remain mere venues for the transmission of a prescribed set of information from teacher educators to pupil- student over a fixed period of time. Rather, these must promote Ïlearning to teach i.e., the acquisition of knowledge and skills that make possible continuous learning over the lifetime. The illiterate of the 21 St Centuries, according to futurist Alvin Toffler, will not be those who cannot read and write, but those who cannot learn, unlearn, and relearn.Every teacher has to know how to use technology, pedagogy and content effectively in their daily classroom teaching. Good teaching is not simply adding technology to the existing teaching and content domain. Rather, the introduction of technology causes the representation of new concepts and requires developing sensitivity to the dynamic transactional relationship reflected in the curriculum designing of TEP.